Citra karya falsafah, nilai, dan etika dalam perkhidmatan awam. (Kuala Lumpur, Malaysia Institut Tadbiran Awam Negara, Malaysia, 1994)
Civil service philosophy, values, and ethics of Malaysia.
In Malay.
Includes bibliographical references (p. 147-148).
Keywords: Civil service ethics -- Malaysia; Civil service -- Malaysia